2021
DOI: 10.1186/s13568-020-01155-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbial keratinase and the bio-economy: a three-decade meta-analysis of research exploit

Abstract: Microbial keratinase research has been on an upward trajectory due to the robustness and efficiency of the enzyme toward various green technological processes that promote economic development and environmental sustainability. A compendium of research progression and advancement within the domain was achieved through a bibliometric study to understand the trend of research productivity, scientific impacts, authors' involvement, collaboration networks, and the advancement of knowledge gaps for future research e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…To overcome the risk associated with the degradation of keratin substrates, the microbial keratinases are studied extensively in bio-cycling of agro-industrial wastes in cost-effective and eco-friendly ways 15 . Keratinase based formulations like Valkerase, Versazyme, CIBENZA, DP100 and FEED-0001 are useful for the improvement of the nutritional values of animal feeds 16 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the risk associated with the degradation of keratin substrates, the microbial keratinases are studied extensively in bio-cycling of agro-industrial wastes in cost-effective and eco-friendly ways 15 . Keratinase based formulations like Valkerase, Versazyme, CIBENZA, DP100 and FEED-0001 are useful for the improvement of the nutritional values of animal feeds 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that diverse keratinases with different molecular weights, optimal pH values, and optimal temperatures are produced by microorganisms. Most microbial keratinases are secreted into the extracellular matrix in the presence of keratin or keratin-containing substrates ( Vidmar and Vodovnik, 2018 ; Nnolim and Nwodo, 2021 ). Some microorganisms are able to produce extracellular and intracellular keratinases simultaneously.…”
Section: Mechanism Of Action For Keratinasementioning
confidence: 99%
“…In addition, as keratin degradation is a complicated step, sample isolation and enriching steps are important to make sure that the desired strains are sustained. Many keratinase-producing strains have been isolated and identified from the environment ( Nnolim and Nwodo, 2021 ).…”
Section: Mechanism Of Action For Keratinasementioning
confidence: 99%
See 2 more Smart Citations